Rhodopseudomonas palustris PSB06 agent enhance pepper yield and regulating the rhizosphere microecological environment - Luo, Luyun; Wang, Pei; Wang, Diandong; Shi, Xiaobin; Zhang, Jingwen; Zhao, Zhixiang; Zeng, Jun; Liao, Jingjing; Zhang, Zhuo; Liu, Yong (Frontiers in Sustainable Food Systems, 2023)
The Rhodopseudomonas palustris (R. palustris) PSB06 can promote crop growth, as it maybe regulates microbial communities in plant root soil, soil physicochemical properties, thus creating a favorable habitat for the crop growth. However, there are few studies on the yields and rhizosphere microbial community of R. palustris PSB06 agent. In the study, the high-throughput sequencing was used to study the changes of rhizosphere soil bacterial community after PSB06 treatment. The results indicated R. palustris PSB06 agent increased the pepper yield by 33.45% when compared to control group, with better effect than other treatments. And it also significantly increased soil nitrogen concentration. R. palustris PSB06 agent had improved pepper rhizosphere bacterial α diversity and changed the community structure. Acidobacteria, Proteobacteria, Actinomycetes and Firmicutes were dominant phyla in all the pepper rhizosphere soil samples. The results showed that soil bacterial community were significantly positively correlated with pH (R = 0.8537, P = 0.001) and total nitrogen (R = 0.4347, P = 0.003). The nine significantly enriched OTU in R.palustris PSB06 treatment (PB) group belong to Nitrososphaera (OTU_109, OTU_14, OTU_18, OTU_8), Lysobacter (OTU_2115, OTU_13), Arenimonas (OTU_26), Luteimonas (OTU_49), and Ramlibacter (OTU_70) were significantly positively correlated with the total yield of pepper (R > 0.5, P < 0.05). Overall, our results provide a theoretical basis for studying the microbial regulation of R.palustris PSB06 on rhizosphere soil.